Perfluorodecalins and Hexenol as Inducers of Secondary Metabolism in Taxus media and Vitis vinifera Cell Cultures - Vidal-Limon, Heriberto R.; Almagro, Lorena; Moyano, Elisabeth; Palazon, Javier; Pedreño, Maria A.; Cusido, Rosa M. (Frontiers in Plant Science, 2018)
Plant cell cultures constitute a potentially efficient and sustainable tool for the production of high added-value bioactive compounds. However, due to the inherent restrictions in the expression of secondary metabolism, to date the yields obtained have generally been low. Plant cell culture elicitation can boost production, sometimes leading to dramatic improvements in yield, as well as providing insight into the target biosynthetic pathways and the regulation of the genes involved. Among the secondary compounds successfully being produced in biotechnological platforms are taxanes and trans-resveratrol (t-R). In the current study, perfluorodecalins (PFDs) and hexenol (Hex) were tested for the first time with Taxus media and Vitis vinifera cell cultures to explore their effect on plant cell growth and secondary metabolite production, either alone or combined with other elicitors already established as highly effective, such as methyl jasmonate (MeJa), coronatine (Coro) or randomly methylated-cyclodextrins (CDs). The total taxane content at the peak of production in T. media cell cultures treated with PFDs together with Coro plus -CDs was 3.3-fold higher than in the control, whereas the t-R production in MeJa and -CD-treated V. vinifera cell cultures increased 552.6-fold compared to the extremely low-yielding control. Hex was ineffective as an elicitor in V. vinifera cell cultures, and in T. media cell suspensions it blocked the taxol production but induced a clear enhancement of baccatin III. Regarding biosynthetic gene expression, a strong positive relationship was observed between the transcript level of targeted genes and taxol production in the T. media cell cultures, but not with t-R production in the elicited V. vinifera cell cultures.